Legally blonde 2 red, white & blonde - Kondell, Kate 1973-; Kent, Rolfe 1963- (Sony Pictures Home Entertainment, 2006)
When she's fired from her job at an upscale law firm for voicing her stance against the testing of cosmetics on animals, Elle heads to Capitol Hill to fight for her cause before Congress. Once there, she runs into plenty of adversity and red-tape and can't seem to find anyone who will listen to her proposals. She meets and befriends an elderly bellman who's been around long enough to know the ins and outs of the political machine. With his help, Elle attempts to convince disillusioned U.S. Representative Rudd to help her get her voice heard in front of the stodgy old coots of the legislative branch
Based on the characters created by Amanda Brown
Originally released as a motion picture in 2003
Special features: Deleted scenes; gag reel; outtakes; "We can" music video with LeAnn Rimes; audio commentary by the cast; "Welcome to Delta Nu" interactive quiz; "Blonde ambition" featurette; photo gallery ; trailers
Keywords: Serienfilm; Filmkomödie; Gerichtsfilm; Liebesfilm; Legal drama; Bills, Legislative / Drama; Bellhops / Drama; Théâtre judiciaire; Bellhops; Bills, Legislative; Drama; Film; DVD-Video